The Therapeutic Effect of miRNA-19a/19b on Heart Failure in Mice and the Mechanism of Myocardial Regeneration and Repair - Jin, Lei (Cellular and Molecular Biology, 2022)
Heart failure is a common cardiovascular disease. The elderly have a high risk of illness. Many patients die of the disease every year. It has become a killer for all humans. Cardiovascular disease often triggers myocardial ischemia and myocardial cell apoptosis, resulting in myocardial damage and even heart failure in patients with cardiovascular disease. Related studies have shown that miRNA-19a/19b plays an important role in myocardial damage and heart failure character. The purpose of this article is to further explore the therapeutic effect of miRNA-19a/19b on heart failure and the regulation mechanism of myocardial regeneration and repair. In this paper, 40 male mice were used as experimental objects to perform ligation surgery on the coronary arteries of mice. To establish an animal model of myocardial infarction and heart failure, then inject miRNA-19a/19b reagent through the tail vein of the mouse, observe the changes of the myocardial cell and the area of the myocardial infarction by immunofluorescence PCR technology, and detect the myocardial tissue in the mouse. Specific changes in the expression of miRNA-19a/19b. The results of the study showed that miRNA-19a/19b can improve the cardiac function of mice. The cardiac function index of mice increased from the original (263.13±5.26) to (385.48±6.92), the area of myocardial infarction decreased by 27.5%, and the proliferation rate of myocardial cells increased by 18.6%, the rate of myocardial regeneration and repair increased by 20.4%. Therefore, it can be seen that miRNA-19a/19b has a significant effect on the treatment of heart failure in mice, can effectively improve heart function, and can promote the regeneration and repair of damaged myocardium, proving the feasibility of miRNA-19a/19b for cardiovascular disease.